LiFePO4 modified Li1.02(Co0.9Fe0.1)0.98PO4 cathodes with improved lithium storage properties - Aravindan, Vanchiappan (2014)
LiCoPO4 and Li1.02(Co0.9Fe0.1)0.98PO4 were prepared by conventional solid state reactions. The surface modification of Li1.02(Co0.9Fe0.1)0.98PO4 particulates by LiFePO4 was successfully carried out by a dry coating procedure. TEM analysis confirmed the presence of a LiFePO4 coating layer of about 20 nm on the surface of the Li1.02(Co0.9Fe0.1)0.98PO4 particles. All three cells delivered high initial discharge capacities of 122, 130 and 128 mA h g−1 for LiCoPO4, Li1.02(Co0.9Fe0.1)0.98PO4, and LiFePO4 modified Li1.02(Co0.9Fe0.1)0.98PO4, respectively. However, these cells presented quite different cycle retention rates after 20 cycles, 21, 22 and 70% for LiCoPO4, Li1.02(Co0.9Fe0.1)0.98PO4, and LiFePO4 modified Li1.02(Co0.9Fe0.1)0.98PO4, respectively. The improved cycle retention of the LiFePO4-modified Li1.02(Co0.9Fe0.1)0.98PO4 resulted from its reduced reactivity towards the electrolyte and the effective prevention of resistive layer formation on the LiCoPO4 surface during high voltage cycling.